Google Translate dan Penerjemahan: Penggunaan Google Translate pada Penerjemahan Teks Bahasa Arab - Dillah Nur Syafanah; Indah Permatasari; Muhammad Rivyal (STIKes Ibnu Sina Ajibarang, 2025)
This study aims to analyze the use of Google Translate in translating Arabic text into Indonesian. The aim is to examine translation accuracy, precision, and the relationship between translation and meaning. A descriptive qualitative method was used to explore the phenomenon in its specific context. Data were taken from classical and modern Arabic texts. The findings show that although Google Translate has seen improvements, it still faces some challenges. These include word-for-word translation, lack of understanding of cultural context, and gender terminology issues. While Google Translate can be a useful tool, it cannot completely replace human translators, especially in translating adverbs and complex grammatical structures. This research emphasizes the importance of translation quality and the role of digital tools in translation. By learning to use these tools effectively, users can improve their translation skills and enhance their ability to communicate across languages. Thus, while machine translation offers convenience and speed, human insight remains essential to achieve nuance, clarity and contextually appropriate meaning in Arabic-Indonesian translation.